Temporal activity patterns of predators and prey across broad geographic scales. (24th October 2018) - Lang, Stephen D J; Mann, Richard P; Farine, Damien R
Abstract : Predators align their hunting effort with the daily activity patterns of prey. Using large citizen-science datasets, we show that bird-eating raptors hunt more at times when songbirds are active rather than when they are vulnerable. This behavior is consistent over broader scales, with the same patterns observed for closely-related predators across 2 continents. Our finding provides insight into the ongoing arms race between predators and their prey. Abstract: Predators and prey are locked in an evolutionary arms race that shapes their behavior and life history. Predators target prey vulnerabilities to maximize hunting success, while prey trade-off foraging against predation avoidance. Though studies have demonstrated how predation risk can alter how prey allocate daily foraging effort, little work has considered the implications of this temporal component of behavior from a predator's perspective, or assessed its influence on broad-scale predator–prey interactions. We develop a method to compare daily activity patterns of avian predators and prey using data from 2 large citizen science datasets collected on different continents. Our analyses reveal evidence for convergent daily hunting strategies across avian predators, with distinct differences according to prey type. By comparing predator data with correspondent data from songbirds, our study suggests that predators (Accipiters) specialized to hunt songbirds match the activity patterns of their prey species. These results indicate predators have evolved common temporal hunting strategies to exploit temporal patterns in prey behavior.